Conveyance of the Dramatic Work El Gran Galeoto by José Echegaray to the European Scene and His Reception in Bratislava at the End of the 19th Century - Laslavíková Jana; Calvo Beatriz Gómez-Pablos (Slovenské divadlo)
This study looks at the work of Spanish playwright José Echegaray and the circumstances of his domestication on the European theatre stages at the turn of the 20th century. One of his most important works, El gran Galeoto55, arrived in Bratislava in 1889, only one year after its premiere in Vienna and three years after the opening of the new building of the Bratislava City Theatre. The premiere of the work, translated into German and in a theatrical adaptation from Paul Lindau’s pen named Galeotto took place around the same time as the premiere of the work Ralph William from the domestic author Josef Julian, which thanks to a similar theme was perceived as «Bratislava’s Galeotto».